Lean management implementation in Malaysian public sector : critical success factors and performance implications - Zarifa Amira, Zulkeflee (2023)
The performance of the Malaysian public sector is facing several significant issues (e.g., service performance, customer satisfaction, operational costs, etc.) caused by the existence of waste (i.e., non-value-added activities) in their service operations. Therefore, this study aims to investigate the effects of lean management implementation on public sector performances along with the critical success factors (i.e., lean resources, lean leadership, lean culture, and lean knowledge management) of its implementation. This cross-sectional quantitative survey collected 131 questionnaires from public organisations in Malaysia that were selected through a stratified random sampling procedure. The population is divided into three strata: federal, state, and local governments, and from each stratum, a random number of samples were chosen from the stratum. Data were analysed by using the structural equation modelling (SEM) approach with SmartPLS professionals. Findings show that lean resources, lean culture, and lean knowledge management are critical success factors that affect the implementation of lean management in the public sector in Malaysia. Lean leadership is not supported as a critical success factor as previous studies have a different point of view when it comes to the top management level in the Malaysian public sector. It happened when the leaders did not fully comprehend the application of lean management, the idea of lean could not reach their subordinates. Subsequently, the holistic implementation of lean management will help the public sector organisations in Malaysia to enhance their performance. Theoretically, this study extends the boundary of knowledge in the field of operations management by looking into public organizations from the perspectives of the resourcebased view and complementarity theories. As a result, practitioners and policymakers could use the insight from this study to tailor strategies for leveraging public sector performance in Malaysia.